The nordic hamstring exercise - is it a part of the weekly training in female elite football? - Linnebjerg, C.; Mette, H.; Bek, C. M.; Bencke, J.; Oxfeldt, M.; Sonne, M. B.; Karlsson, M.; Hölmich, P.; Zebis, M. K. (British Journal of Sports Medicine, 2021)
Background The hamstring muscle strengthening is an integral part of validated injury prevention programs in football. However, it is unknown whether hamstring muscle strengthening exercises are used in female elite football.